(untitled) (Journal of NELTA, 2021)
Unwanted behaviours of students that impede the normal functioning of the classroom has become a centre of concern of the majority of the teachers and university teachers are also no exception to this matter. This paper is an attempt to explore teachers’ approaches and strategies in dealing with “disruptive” behaviour in Nepalese university classrooms. Using non-random sampling, 15 university teachers who have more than five years of teaching experience in the corresponding fields were chosen as the participants of the study. The tools for data collection were an open-ended questionnaire and a semi structured interview and they were administered following all ethical considerations. The study, based on Dreikurs’s mistaken model for classroom management (1968), found that teachers divided teachers’ talking time (TTT) and students’ talking time (STT), minimized their talking time, played an instrumental role in not allowing students to divert the academic discussion into non-academic ones. Then, the teachers and students collectively formulated dos and don’ts before the semester began and whenever there was a disruption in most of the contexts, those rules and regulations were acknowledged and stopped students from monopolizing classroom discussion.